Pendidikan Karakter Siswa dalam Membangun Generasi Islami di SMP IT - Muaini Muaini; Nurani Nurani; Siti Nurfiati; Yeni Khairunnisa; Dhyafatusholehah Dhyafatusholehah; Dini Andryani; Muhammad Izam Hari; Wahyu Regal Putra; Mawar Mawar (Pendekar: Jurnal Pendidikan Berkarakter, 2025)
Abstract: This study aims to determine the character education of students in forming an Islamic Generation at IT Junior High School which will form students' noble morals. The research method used in this research is the kuliatatif method. Extracting data from direct observation, interview sources as information from the principal, teachers, students and documentation. Data analysis uses the theory of Miles and Hubermen which has several procedures in analyzing data, namely; data collection, data reduction, data presentation, data conclusion/verification. The results showed that student character education, can be seen from honesty, responsibility, care for the environment, relationships with parents, care for rules, discipline and the habit of praying in congregation, has a significant influence on the creation of a positive learning environment at IT Junior High School. Character education can help students be more productive in learning, more organized, and more responsible for academic tasks. Schools should continuously integrate character education on honesty and responsibility in the curriculum and extracurricular activities to strengthen values such as honesty, responsibility, discipline, and care for the environment. Teachers always set a good example in terms of honesty and responsibility at school and reward students who show positive behavior. Parents also play an active role in educating children about the importance of honesty and responsibility, both at home and in their daily lives.Abstrak: Penelitian ini sangat penting karena pendidikan karakter memiliki peran yang sangat krusial dalam membentuk generasi Islami yang memiliki akhlak mulia di SMP IT, pendidikan karakter tidak hanya bertujuan untuk mengembangkan kecerdasan akademik, tetapi juga untuk membentuk sikap dan perilaku yang sesuai dengan nilai-nilai Islam. Metode penelitian yang yang mengunakan dalam penelitian ini adalah metode kuliatatif. Mengali data dari observasi langsung, wawancara narasumber sebagai informasi kepala sekolah, terdapat 5 guru, 75 siswa dan dokumentasi. Analisis data mengunakan teori Miles dan Hubermen yang memiliki beberapa prosedur dalam menanlisis data yaitu; pengumpulan data, reduksi data, penyajian data, kesimpulan/verifikasi data. Hasil penelitian menunjukkan bawa pendidikan karakter, seperti kejujuran, tanggung jawab, kependulian terhadap lingkungan, kedisiplinan, dan kebiasaan sholat berjamaah, berpengaruh besar dalam menciptakan lingkungan belajar yang positif di SMP IT. Pendidikan karakter ini membuat siswa lebih produktif, teratur, dan bertanggung jawab.sekolah perlu terus mengintegrasikan nilai-nilai tersebut dalam kurikulum dan kegiatan ekstrakurikuler. Guru harus memberikan contoh yang baik dan menghargai siswa yang menunjukkan perilaku positif. Orang tua juga memiliki peran penting dalam mendidik anak-anak mengenai nilai- nilai tersebut di ruma.